Optune in Glioblastoma: Revolutionizing Treatment with Tumor Treating Fields - Długozima, Patrycja; Mączewska, Klaudia; Hakało, Dominika; Kozakiewicz , Julia; Kościelecki , Kamil; Kalisz , Agnieszka; Skorulska , Iwona; Grzeszczuk , Paulina; Grywińska , Weronika; Głowacka , Aleksandra (Quality in Sport, 2025)
Introduction: Glioblastoma multiforme (GBM) is one of the most aggressive primary brain tumors in adults, known for its rapid progression and poor prognosis. Despite advancements in surgical resection, radiotherapy, and chemotherapy, the median survival for GBM patients remains limited. In recent years, Tumor Treating Fields (TTFields), commercially known as Optune, have emerged as an innovative, non-invasive therapeutic approach. TTFields utilize alternating electric fields to interfere with the mitotic processes of cancer cells, thereby inhibiting tumor growth. This paper aims to provide an in-depth review of the current understanding of TTFields therapy, assess its clinical efficacy, and explore future directions in GBM management. Materials and methods: A systematic literature review was conducted, focusing on peer-reviewed articles published between 2017 and 2025. The search was performed using databases such as PubMed, JAMA, Lancet Oncology, Neuro-Oncology etc. Keywords included “glioblastoma,” “Tumor Treating Fields,” “Optune,” “clinical trials,” and “survival outcomes”. Summary: The integration of TTFields therapy into the standard GBM treatment regimen represents a significant advancement in neuro-oncology. Clinical evidence indicates that TTFields, particularly in combination with temozolomide, can extend survival and delay disease progression in GBM patients. Conclusions: TTFields therapy has emerged as a promising adjunctive treatment for glioblastoma, offering new hope for patients facing this highly aggressive disease. While current data support its efficacy and safety, further large-scale studies are needed to refine treatment protocols, identify predictive biomarkers, and assess long-term benefits. As research advances, TTFields may become an integral part of multimodal glioblastoma therapy, potentially improving both survival rates and quality of life for patients.